Marine spatial planning for connectivity and conservation through ecological corridors between marine protected areas and other effective area-based conservation measures - Podda, Cinzia; Porporato, Erika M. D. (Frontiers in Marine Science, 2023)
Maritime Spatial Planning (MSP) promotes the sustainable human activities development and uses in the marine space, playing a role in their effective management. The enhancement of connectivity is crucial for the conservation of biodiversity and landscape planning. Ecological Corridors (ECs) are an important type of connectivity for biodiversity conservation in fragmented habitats. The EU Biodiversity Strategy 2030 includes ECs into the network of protected areas and allows for the creation of additional protected areas. MSP studies considering ECs remain still lacking, especially for the design of networks between Marine Protected Areas (MPAs) and Other Effective area-based Conservation Measures (OECMs). In this paper, knowledge, and tools for investigating marine ECs were reviewed, with a systematic bibliometric analysis to summarize the current scientific research. Previous studies integrating ecological connectivity into planning for marine conservation have focused on models of larval dispersal, adult movements, and dispersal of single species by using benthic habitat proxies. Few studies were found on ECs in marine environments: in the coral Caribbean reef systems in the Gulf of Mexico; within benthic habitats along the Pacific coast of Canada; between MPAs in British Columbia (Canada); and by analyzing migratory species in the Yangtze estuary (China). Commonly used approaches to project and map ECs in marine environments are least-cost and circuit theories allowing to incorporate movement with cost or resistance to movement, depending on species and preferred habitats. The systematic bibliometric analysis returned 25 studies, most of which were from North America (40%) and European countries (36%) and the largest share of papers (68%) from 2018 to 2022. This review pinpointed the need of integrating different disciplines to investigate connectivity and the need by policymakers and practitioners to recognize the importance of ecological connectivity, even there are significant challenges for integrating connectivity into policies, planning, and conservation.